Attenuation of hemodynamic responses to laryngoscopy and endotracheal intubation by intravenous esmolol - KN, Gurudatta; Mallappa, Kiran; GL, Ravindra (International Journal of Research in Medical Sciences, 2017)
Background:Sympathetic response associated with laryngoscopy and endotracheal intubation is a potential cause for a number of complications especially in patients with cardio-vascular compromise. The aim of our study was to evaluate and study the efficiency of intravenous esmolol in the attenuation of hemodynamic response to laryngoscopy and intubation in normotensive individuals. Methods:100 surgical patients of either sex of physical status ASA I/II were randomly divided into 2 groups. Group C (10 ml of 0.9% normal saline) and group E (Esmolol 100 mg IV) given 2 minutes before induction. Baseline parameters - heart rate, systolic blood pressure, diastolic blood pressure and rate pressure product were noted at baseline level, just before induction, 1 min., 3 min., 5 min and 10 minutes after tracheal intubation. Results:Intravenous esmolol showed statistically significant attenuation of hemodynamic response to laryngoscopy and intubation when compared with the control. Conclusion:We conclude that esmolol in a dose of 100 mg given 2 minute before induction is highly effective in attenuation hemodynamic response to laryngoscopy and intubation.